Regeneration of submediterranean species Euonymus latifolius (L.) Mill. at its southernmost limit in Europe - Agea, Daniel; García-de Lucas, Sandra; Lorite, Juan (Mediterranean Botany, 2021)
Due to the ongoing effects of climate change in the Mediterranean (increasing temperature and decreasing rainfall), conditions for Submediterranean species are disappearing as their habitats are dwindling. We have focused on Euonymus latifolius (L.) Mill., a nemoral-Submediterranean species, at its southernmost populations of Europe. The aim was to evaluate the population structure and regeneration niche of the species at microhabitat scale. We selected five larger populations among the 13 existing ones, marking 25-30 individuals per population. We measured twice: height, width, vegetation cover, survival, soil moisture and temperature. As result, we provided data of the 13 existing populations, containing 93 adults and 350 juveniles. Moreover, we have obtained a very skew population structure with a low number of recruits for five selected populations, especially at smaller populations. Most E. latifolius juveniles were encountered under dense tree canopy (more than 80 % in cover) formed by a mixture of Submediterranean and Mediterranean species. Biovolume per population showed significant differences among the main populations CP and CV, presenting this last a higher recruitment, while recruitment was very low in general. For soil parameters, we found a critical role of canopy, which showed a positive effect on juvenile microhabitat (higher moisture and lower soil temperature). The results showed us the critical situation of the species, with very fragmented populations, low number of individuals, and scattered spatial patterns of individuals within the populations. Also, survival problems, a non-balance demographic structure, and regeneration problems were detected. Finally, we propose a sere of conservation measures, from monitoring to active measures (key tree species plantation, reintroduction, reinforcements), combined with threat control (herbivory, pests, and impact from outdoor activities). All combined may help to preserve this species at its southernmost populations.